Effective risk assessment tools for osteoporosis in the Indian menopausal female - Seema Sharma; Sunila Khandelwal (Wolters Kluwer Medknow Publications, 2010)
Objectives: This study was designed to assess the effectiveness of self-administered osteoporosis risk score sheet, body mass index (BMI), and bone mineral density (BMD) (ultrasound) in screening females with low bone mass, and how the results of the tools correlate with each other. Materials and Methods: The study was conducted on 536 postmenopausal women, who attended public awareness camps on Midlife Women Health held at the Menopause Research Unit, MGMCH, Sitapura, Jaipur. At these camps, in addition to several informational sessions on issues related to menopause, ultrasonic measurement of BMD was conducted on each participant. A broad questionnaire to identify midlife health problems was developed, and osteoporosis specific score sheet was designed to be self-administered. Patients were required to complete the osteoporosis specific risk score sheet and women health questionnaire (WHQ). BMI was determined. Statistical analysis was carried out to find the correlation between various variables. Sensitivity and specificity of the each risk score ascertained and cutoff risk score for identifying osteopenia was derived by comparing area under curve of each risk score on drawing receiver operational curve (ROC). Results: Sensitivity of risk score system was calculated to be 78.33% with 95% confidence interval being 73.24-82.86% and specificity was 27.12% with 95% confidence interval being 21.56-33.27%, keeping the cutoff point at nine. There was statistically significant inverse relationship between risk score and BMD values with Pearson correlation coefficient of (-) 0.22 and positive relationship between BMD and BMI with correlation coefficient of 0.192. Conclusion: By noting down the risk factors and BMI, we can screen out the women who require further evaluation and management, thus, it is an effective tool, particularly in developing countries like India, where most of the patients cannot afford expensive DEXA scans, although considered as the gold standard for BMD assessment. With the help of such scoring systems, health resources can be judiciously utilized.